Contextual Learning-Oriented Animated Cartoons on Student Learning Outcomes in Mathematics Subjects - Ni Ketut Wiswandewi; I Gusti Ayu Tri Agustiana; Putu Ari Dharmayanti (Jurnal Pedagogi dan Pembelajaran, 2026)
Mathematics is a fundamental subject that plays an important role in developing elementary school students' critical thinking, creativity, and problem-solving skills. Students' perceptions of mathematics as a difficult, boring, and uninteresting subject remain a challenge, resulting in low learning motivation and achievement. This study aimed to develop and analyze the validity, practicality, and effectiveness of a 2D Animated Cartoon learning media based on Contextual Learning for the topic of whole number operations among second-grade elementary school students. This study employed a Research and Development (R&D) approach using the ADDIE model (Analyze, Design, Development, Implementation, and Evaluation) and involved 30 second grade students as the trial participants. Data were collected through questionnaires and tests using rating scale assessment sheets and pretest–posttest instruments, and were analyzed using qualitative descriptive and quantitative descriptive techniques. The findings indicated that the 2D Animated Cartoon learning media based on Contextual Learning met the criteria of validity, practicality, and effectiveness, thereby improving students' mathematics learning outcomes. The study concludes that the developed media is feasible to be used as an alternative instructional medium for mathematics learning in elementary schools. The findings also imply that the 2D Animated Cartoon learning media based on Contextual Learning can support more engaging, meaningful, and student centered learning while serving as a reference for teachers in developing technology based instructional media.